2002
DOI: 10.1302/0301-620x.84b5.0840692
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial total wrist replacement in patients with rheumatoid arthritis

Abstract: We have implanted 76 biaxial total wrist prostheses as a primary procedure in patients with rheumatoid arthritis of the wrist. A total of 66 was reviewed at a mean follow-up time of 52 months. Pain was relieved in 67% of the surviving wrist replacements. On the basis of the Hospital for Special Surgery scoring system, 49 wrists (74%) were graded as fair to excellent. More than half of the 27 patients who had an arthrodesis on the contralateral wrist would have preferred a second arthroplasty. Five replacements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 0 publications
0
33
0
4
Order By: Relevance
“…There were radiolucent zones in 4 of 17 cases with a mean follow-up time of 6 years, without other signs of implant loosening. Takwale et al (2002) re-examined 76 Biaxial TWAs with a mean follow-up time of 4 years. Implant survival was 0.86 and 14 more cases showed radiographic signs of prosthetic loosening, but it was not reported whether osteolysis was associated with subsidence or angulation of the implant components.…”
Section: Discussionmentioning
confidence: 99%
“…There were radiolucent zones in 4 of 17 cases with a mean follow-up time of 6 years, without other signs of implant loosening. Takwale et al (2002) re-examined 76 Biaxial TWAs with a mean follow-up time of 4 years. Implant survival was 0.86 and 14 more cases showed radiographic signs of prosthetic loosening, but it was not reported whether osteolysis was associated with subsidence or angulation of the implant components.…”
Section: Discussionmentioning
confidence: 99%
“…Survival at 5 years was 83% with revision as an endpoint and 75% of patients had complete relief of pain and function at the wrist [3]. Stanley and Tolat [6], in their series of 50 Swanson wrist implants with an average follow-up period of 8 years (range 6-11.8), found that two-thirds of patients had a good-to-excellent result assessed by a summary score including pain, patient satisfaction function, and wrist motion [1,4].…”
Section: Discussionmentioning
confidence: 99%
“…Various generations of primary total wrist replacement have been devised and many authors have reported their experience [1][2][3][4][5]. Complications of total wrist replacement include loosening, infection, dislocation, tendon rupture, ulnar deviation, and imbalance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Operationstechnik war die gleiche wie bei Beckenbaugh. Die distale Komponente wurde jeweils zementiert.Bei einer späteren Nachuntersuchung[16] konnten in der gleichen Klinik von den im Zeitraum 1992 bis 1999 implantierten 76 BIAX-Prothesen bei 73 Rheumapatienten insgesamt 66 Prothesen bei 63 Patienten nach viereinhalb Jahren ( bis 8 Jahre) nachuntersucht werden. Es wurde die distale Komponente bei 79% zementiert und nur in der Anfangszeit die proximale bei 14%.…”
unclassified